Isolation and Culture of Skeletal Muscle Myofibers as a Means to Analyze Satellite Cells - Keire, Paul (2013)
Multinucleated myofibers are the functional contractile units of skeletal muscle. In adult muscle, mononuclear satellite cells, located between the basal lamina and the plasmalemma of the myofiber, are the primary myogenic stem cells. This chapter describes protocols for isolation, culturing and immunostaining of myofibers from mouse skeletal muscle. Myofibers are isolated intact and retain their associated satellite cells. The first protocol discusses myofiber isolation from the flexor digitorum brevis (FDB) muscle. These short myofibers are cultured in dishes coated with PureCol collagen (formerly known as Vitrogen) using a serum replacement medium. Employing such culture conditions, satellite cells remain associated with the myofibers, undergoing proliferation and differentiation on the myofiber surface. The second protocol discusses the isolation of longer myofibers from the extensor digitorum longus (EDL) muscle. Different from the FDB preparation, where multiple myofibers are processed together, the longer EDL myofibers are typically processed and cultured individually in dishes coated with Matrigel using a growth factor rich medium. Under these conditions, satellite cells initially remain associated with the parent myofiber and later migrate away, giving rise to proliferating and differentiating progeny. Myofibers from other types of muscles, such as diaphragm, masseter, and extraocular muscles can also be isolated and analyzed using protocols described herein. Overall, cultures of isolated myofibers provide essential tools for studying the interplay between the parent myofiber and its associated satellite cells. The current chapter provides background, procedural, and reagent updates, and step-by-step images of FDB and EDL muscle isolations, not included in our 2005 publication in this series.